(untitled) (Biological Sciences - PJSIR, 2022)
The probiotic properties of Lactobacillus isolates of traditional yoghurt were investigated during the study. For that seven species of Lactobacillus were identified phenotypically. Out of 84 isolates, 23 acidophilus, 21 L. casei, 11 L. helveticus, 09 each L. delbrueckii sub sp. bulgaricus and L. delbrueckii sub sp. lactis, 03 L. viridescense and 02 L. plantarum were identified. All of these identified species were screened for antibacterial activity against foodborne pathogens, acid and bile tolerance and antibiotic resistance pattern. The results indicated that L. casei S66, L. delbrueckii sub sp. bulgaricus S65, L. acidophilus S26 and L. plantarum S19 produced antimicrobial substances against the indicator organisms and showed tolerance against acidic pH of 2.5 and survival against the bile salt concentration of 0.1 and 0.2. The L. acidophilus S26 survived the 0.3% bile salt concentration and was resistant to antibiotics ciprofloxacin, kanamycin, penicillin and vancomycin.